2004
DOI: 10.1021/jp049224k
|View full text |Cite
|
Sign up to set email alerts
|

Intensities of IR Stretching Bands as a Criterion of Polarization and Initial Chemical Activation of Adsorbed Molecules in Acid Catalysis. Ethane Adsorption and Dehydrogenation by Zinc Ions in ZnZSM-5 Zeolite

Abstract: A DRIFT study of ethane adsorbed by zinc cations in ZnZSM-5 prepared by chemical reaction of the hydrogen form of the zeolite with zinc vapor at 770 K, or by wet ion exchange, reveals unusual spectra of adsorbed C2H6 species. In addition to the weakly perturbed narrow bands in the region of C-H stretching vibrations, these spectra exhibit a very intense broad IR band with a frequency that is more than 200 cm(-1) lower than those of the C-H stretching vibrations of gaseous or physically adsorbed ethane. The ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
140
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 19 publications
14
140
0
Order By: Relevance
“…Obviously, the perturbation and polarization of the other C-H bonds are much weaker. These results are similar to those earlier reported in our study [2] on ethane adsorption by Zn +2 ions in ZnZSM-5 zeolite, where it was also shown that polarization of adsorbed molecules was followed by heterolytic dissociative adsorption at elevated temperatures.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Obviously, the perturbation and polarization of the other C-H bonds are much weaker. These results are similar to those earlier reported in our study [2] on ethane adsorption by Zn +2 ions in ZnZSM-5 zeolite, where it was also shown that polarization of adsorbed molecules was followed by heterolytic dissociative adsorption at elevated temperatures.…”
Section: Resultssupporting
confidence: 93%
“…[1][2][3] such new spectral approach was supported by our experimental results on adsorption of methane and ethane by ZSM-5 zeolite modified with Zn +2 cations. In these studies we demonstrated that, at elevated temperatures, the most intense C-H vibrations which correspond to the stretching of the highly polarized C-H bonds of molecules adsorbed by the coordinatively unsaturated zinc cations are involved into subsequent heterolytic dissociative adsorption via abstraction of protons by the adjacent basic oxygen atoms.…”
Section: Introductionmentioning
confidence: 63%
“…In contrast, unlike adsorption of light paraffins on the Lewis sites that has been previously studied by us in Refs [2,3], formation of the π-complexes has practically no influence on intensities of the fundamental bands from C-H stretching vibrations. This indicates the absence of polarization of C-H bonds in the π-bonded species which are not involved into reaction coordinate of proton transfer to adsorbed ethylene.…”
Section: Figurementioning
confidence: 73%
“…Bearing this in mind, in previous work [2,3] we proposed using intensities of C-H IR stretching bands as measures of the polarization of adsorbed light paraffins by the low-coordinated cations in zeolites. The obvious advantage of this new spectral approach lies in the closer connection of the intensities of IR bands with polarization of C-H chemical bonds on stretching via vibrational excitation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by reacting bridging hydroxyl groups in high-silica zeolites with vapours of metallic Zn (Kazansky & Serykh 2004;Kazansky & Pidko 2005a;Pidko & Kazanskii 2005) and Cd (Serykh 2005) at a high temperature, their quantitative replacement by bare Zn 2+ and Cd 2+ cations at the zeolitic exchange sites was achieved. However, owing to the inhomogeneous distribution of pairs of framework aluminium, a substantial variation in the chemical reactivity of the introduced cationic species was observed.…”
Section: Introductionmentioning
confidence: 99%